2018
DOI: 10.1002/hbm.24288
|View full text |Cite
|
Sign up to set email alerts
|

The neural underpinnings of cross‐cultural differences in creativity

Abstract: Whereas Western individualistic cultures emphasize uniqueness, collectivistic East-Asian cultures discourage it. Here we examined whether cross-cultural differences in creativity as measured by a task of divergent thinking (DT) are explained by enhanced activity in brain regions that mediate inhibitory control (e.g., the left inferior frontal gyrus [L-IFG]). We therefore predicted that the L-IFG would be "hyperactive" among individuals from East-Asian cultures compared to Western ones. In Study 1, Israeli and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 119 publications
0
19
0
1
Order By: Relevance
“…Future studies could empirically investigate the roles of culture, including but not limited to multicultural experiences and language learning, that have emerged in the past 10 years in underwriting the conceptualization, processing, and assessment of creativity. Additionally, other studies could take greater efforts to demystify the cross-cultural neural underpinning of creativity using high-density brain potentials or neuroimaging measures, given that two recent studies have started to explore the neural correlates of cross-cultural differences in creativity (Ivancovsky et al., 2018, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Future studies could empirically investigate the roles of culture, including but not limited to multicultural experiences and language learning, that have emerged in the past 10 years in underwriting the conceptualization, processing, and assessment of creativity. Additionally, other studies could take greater efforts to demystify the cross-cultural neural underpinning of creativity using high-density brain potentials or neuroimaging measures, given that two recent studies have started to explore the neural correlates of cross-cultural differences in creativity (Ivancovsky et al., 2018, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Benedek et al (2018) showed that creating new ideas was associated with increased activation of the left SMG, supporting the role of the SMG in the left anterior IPL with generation of original ideas. The IPL has previously been associated with the use of the DMN in divergent thinking (Heinonen et al, 2016), and has been said to play a role, alongside other parts of the DMN, in producing new combinations important for originality during the creative process (Buckner, Andrews‐Hanna, & Schacter, 2008; Ellamil, Dobson, Beeman, & Christoff, 2012) with Ivancovsky et al (2018) findings higher creativity in the generation phase of the AUT was associated with greater activation of the IPL, This area has also been previously associated with the verbal generation of ideas, and episodic memory retrieval during generation (Bechtereva et al, 2004; Mathias Benedek, Jauk, et al, 2014). The AUT task involves manipulation of common objects to find creative uses for them, and as previously mentioned the IPL is activated in these tasks.…”
Section: Introductionmentioning
confidence: 99%
“…This may be because standard control tasks, such as object characterisation, also rely on the semantic control system, and so activity related to divergent thinking is not strong enough to survive the contrast. However, several studies have found an inhibitory role of the IFG (Beaty et al, 2016; Ivancovsky, Kleinmintz, Lee, Kurman, & Shamay‐Tsoory, 2018) with Kleinmintz et al (2017) suggesting evaluating original ideas was related to an increase in activation in the left IFG, whereas generating original ideas was related to inhibition of the left IFG.The IFG has also been said to control activation in the middle temporal gyrus (MTG) said to be important in both the semantic and default mode network (DMN), with Vartanian et al (2018) suggesting the IFG selects ideas that are generated by the MTG to produce responses consistent with the task demands.…”
Section: Introductionmentioning
confidence: 99%
“…Pembiasaan demikian melatih dan membentuk area otak anterior cingulate cortex (ACC) menjadi kuat (Pornpattanangkul et al, 2016). Anterior cingulate cortex (ACC) telah dilaporkan para ahli sebelumnya bahwa area otak ini berfungsi sebagai kontrol emosi dan kognitif yang ditunjukkan melalui performansi inhibitory control (Ivancovsky et al, 2018).…”
Section: Penutupunclassified